The Level of awareness of green marketing and its managerial implications amongst selected South African manufacturing Small, Medium and Micro Enterprises (SMMEs) in KwaZulu–Natal - LEKHANYA, Lawrence Mpele (Journal of Economics and Behavioral Studies, 2014)
The focus of this paper is to present an exploratory study on the level of awareness regarding green marketing and its managerial implications, among selected, South African Manufacturing Small, Medium and Micro Enterprises (SMMEs), in the province of KwaZulu–Natal (KZN). The concept of green marketing and thought provoking managerial implications are still an issue of concern in the South African manufacturing sector. The study aimed to explore the awareness levels about green marketing by selected South African manufacturing SMMEs in KZN, and the resulting managerial implications. Primary data was collected from 84 manufacturing SMMEs. This research was quantitative in nature and a questionnaire was used to collect data from SMMEs owners/managers in KZN. Findings of the research indicate that SMMEs in the study are aware of green marketing and its managerial implications. It further reveals that SMMEs’ owners/managers indicate that the South African Environmental Act and Consumer Protection Act are additional factors that influence their businesses operations. The paper will benefit SMMEs owners/managers, SMMEs marketing managers, and affiliated stakeholders, by introducing a new understanding of green marketing and how to cope with the demand of new green marketing strategies. Most work on the Green Zone has concentrated on green products, with little emphasis on green marketing and its implications. The findings are limited by the study’s exploratory, quantitative nature and small sample. Generalisation should be done with care and further research, with a large sample and consideration of other provinces, is therefore recommended.